WRITING AND INTERSECTIONALITY IN THE SHORT STORIES OLHOS D’ÁGUA AND KISS IN THE FACE OF CONCEIÇÃO EVARISTO - Silva Souza, André; Luiza Cangussu Silva, Paula; Rocha da Silva, Claudia (Revista Gênero e Interdisciplinaridade, 2024)
Data from the Brazilian Public Security Forum (FBSP), in the year 2022, indicate that on average 04 women are victims of femicide daily. Female domestic workers number a total of 5.2 million, 65% of whom are black. Considering these data, this work aims to analyze the alarming continuity of forms of oppression against these women, based on qualitative research, from the perspective of literature and the concepts of writing and intersectionality, in the short stories Olhos d’água and Beijo na face , by Conceição Evaristo, highlighting issues of race, gender and class. Theoretical discussions are supported by Angela Davis (2016), Conceição Evaristo (2016), Patricia Hill Collins and Sirma Bilge (2021). From the analysis of the stories, it is possible to affirm the existence of a perpetuation of class, gender and racial inequalities and violence, in an intersectional way, as well as realizing how much writing in literature has been a form of denunciation and resistance in women’s daily lives. black.